(569) Time Sharing and Incremental Computation تقاسم الوقت والحساب التدريجي - Lombardi, A. Lionello (INP, 2024)
This paper contains a proposal for the design of bulk storage devices suitable for multiple-access computers. Some kind of bulk storage would also -1- allow for implementation effective extensions of memory by means of "page turning" techniques, -2- on-line real time management information systems roughly as inexpensive as batch processing systems.